Plant diversity of ceremonial foods used by Minangkabau ethnic group in West Sumatra, Indonesia - NAHDA KANARA; HADI SUSILO ARIFIN; ERVIZAL AMIR MUHAMMAD ZUHUD; BAMBANG PRAMUDYA NOOROCHMAT (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kanara N, Arifin HS, Zuhud EAM, Noorochmat BP. 2025. Plant diversity of ceremonial foods used by Minangkabau ethnic group in West Sumatra, Indonesia. Biodiversitas 26: 6352-6366. Ethnic communities generally possess Traditional Ecological Knowledge (TEK) in managing natural resources and the environment as well as traditonal ceremonies and foods. This study is the first that comprehensively document plant diversity for ceremonial foods by Minangkabau communities in West Sumatra, Indonesia. The objectives are to: (i) identify the ceremonial food plants, (ii) analyze the cultural food significance of ceremonial food plant species, and (iii) analyze the important local agroforestry system to conserve the ceremonial food plants used by the Minangkabau ethnic group. Data collection was performed using purposive sampling and ethnobotanical approaches. The information was obtained through semi-structured interviews with 104 informants in Lima Puluh Kota District and Payakumbuh Municipality, West Sumatra, Indonesia. Valuation of the key plant species was obtained using the Cultural Food Significance Index (CFSI) method. The data show that Minangkabau ethnic group use 86 taxa from 38 families as ceremonial foods with the dominance family is Solanaceae. Total 30 taxa from 13 family were considered to have a very high-CFSI with the dominance families are Fabaceae and Zingiberaceae. Plants often used in ceremonies by the Minangkabau ethnic group are mostly gathered in the mixed garden and homegarden, showing that local agroforestry systems are the most potential landscape in conserving ceremonial food plants. Maintain local agroforestry systems and preserve socio-cultural practices in Minangkabau ethnic group have implication for the conservation of local food plants and enhance local food security.